Relationship between parenting styles, academic performance and socio-demographic factors among undergraduates at Universiti Putra Malaysia - Che Hassan, Norlizah; Hew, Min Sen (Human Resource Management Academic Research Society, 2017)
The purpose of this study is to determine the relationship between parenting styles, undergraduates’ academic performances and socio-demographic factors (ethnic group and socioeconomic status) among undergraduates at Universiti Putra Malaysia (UPM). This is a cross sectional survey research, which involved 302 undergraduates from Universiti Putra Malaysia (UPM). The instrument of Parenting Authority Questionnaire (PAQ) from Buri (1991) was used to measure the undergraduates’ perceived parenting style. The collected data was analyzed using Statistical Packages for Social Science (SPSS). The findings showed there was a significant negative relationship between authoritarian parenting style and undergraduates’ academic performance (r = -0.160*), but no significant relationship between academic performance and the other two parenting styles, which were authoritative and permissive parenting style. Chi-square test showed that there was no significant difference in parenting styles among the undergraduates in term of ethnic group (Pearson X² (6, N=302) = 4.520, p > 0.05), as well as socioeconomic status (Pearson X² (6, N=302) = 4.249, p > 0.05). This study showed that authoritarian parenting style is negatively correlated with academic performance. Hence, recommendations are given to parents, tertiary education institution and educators.